2022
DOI: 10.1016/j.regg.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac complications in a geriatric population hospitalized with COVID-19: The OCTA-COVID cohort

Abstract: Introducción: La población geriátrica es especialmente vulnerable a la enfermedad por coronavirus (COVID-19) y sus posibles complicaciones. Nos propusimos analizar la incidencia de complicaciones cardiológicas en una población anciana hospitalizada por COVID-19. Métodos: Estudio longitudinal observacional prospectivo que incluyó a pacientes ≥ 75 años con diagnóstico de COVID-19 ingresados en el Servicio de Geriatría de marzo a mayo de 2020. Se recogieron variables epidemiológicas, geriátricas, clíni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…We identified 4710 records through PubMed, EMBASE, and ScienceDirect database searches. A total of 51 articles (i.e., 33,573 patients) were selected for analysis based on the inclusion and exclusion criteria [ 6 , 15 , 16 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The study selection process was documented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We identified 4710 records through PubMed, EMBASE, and ScienceDirect database searches. A total of 51 articles (i.e., 33,573 patients) were selected for analysis based on the inclusion and exclusion criteria [ 6 , 15 , 16 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The study selection process was documented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A study by Katsoularis et al revealed the odds ratio of stroke in COVID-19 patients is 3.63 (1.69 - 7.80) [ 66 ]. In a prospective study by Mónica et al, 17 (5.6%) of COVID-19 patients developed acute pulmonary embolism [ 21 ]. This is similar to the findings by Corrado et al, where 7.7% of COVID-19 patients developed thromboembolism.…”
Section: Reviewmentioning
confidence: 99%
“…This is similar to another retrospective study that revealed new-onset atrial fibrillation in 12.7% of the COVID-19 patients studied. Also, in a study by Mónica et al, 6.5% of the patients developed new-onset atrial fibrillation [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…[13] Similarly, cardiovascular complications such as congestive heart failure, atrial fibrillation, pulmonary embolism and acute coronary syndrome are high among the elderly patients with COVID-19 which result in longer hospital stay and increased mortality. [14] In addition, there are several other risk factors which may contribute to ICU admission among the elderly patients with COVID-19. [15] Numerous studies have been conducted on different aspects of COVID-19; however, the literature on association of comorbidities with ICU admission among the elderly patients with COVID-19 is lacking from Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Similarly, cardiovascular complications such as congestive heart failure, atrial fibrillation, pulmonary embolism and acute coronary syndrome are high among the elderly patients with COVID-19 which result in longer hospital stay and increased mortality. [ 14 ] In addition, there are several other risk factors which may contribute to ICU admission among the elderly patients with COVID-19. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%